Platelet-rich plasma for osteoarthritis treatment - Knop,Eduardo (2016)
ABSTRACT We conducted a comprehensive and systematic search of the literature on the use of platelet-rich plasma (PRP) in the treatment of osteoarthritis, using the Medline, Lilacs, Cochrane and SciELO databases, from May 2012 to October 2013. A total of 23 studies were selected, with nine being controlled trials and, of these, seven randomized, which included 725 patients. In this series, the group receiving PRP showed improvement in pain and joint function compared to placebo and hyaluronic acid. The response lasted up to two years and was better in milder cases. However it was found that there is no standardization in the PRP production method, neither in the number, timing, and volume of applications. Furthermore, the populations studied were not clearly described in many studies. Thus, these results should be analyzed with caution, and further studies with more standardized methods would be necessary for a more consistent conclusion about the PRP role in osteoarthritis.